1994
DOI: 10.1128/iai.62.12.5261-5266.1994
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody that recognizes phosphatidylinositol inhibits induction of tumor necrosis factor alpha by different strains of Plasmodium falciparum

Abstract: The clinical symptoms of human malaria are mediated, at least in part, by the release of tumor necrosis factor alpha (TNF) by monocytes and macrophages. We have found that lysates of Plasmodium falciparuminfected erythrocytes stimulate the secretion of TNF from human mononuclear cells, and we have generated several immunoglobulin M monoclonal antibodies (MAbs) that inhibit the induction of TNF by such lysates. Here we describe the properties of MAb 5AB3-11, which causes dose-dependent inhibition of the TNF-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 18 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…While the number of such combinations in humans is not well understood, it could be up to at least one hundred. Such glycophospholipid determinants are differentially recognized by antibodies, 154,155 as has also been shown recently for serum antibodies in patients with malaria using microarray analyses of synthetic GPI glycoconjugates. 156 In summary, while the total number of glycolipid determinants in glycosphingolipids and glycophospholipids is difficult to estimate, for the considerations here we will assume that the glycolipid repertoire of glycan determinants is B500.…”
Section: How Many Glycan Determinants Exist?supporting
confidence: 53%
“…While the number of such combinations in humans is not well understood, it could be up to at least one hundred. Such glycophospholipid determinants are differentially recognized by antibodies, 154,155 as has also been shown recently for serum antibodies in patients with malaria using microarray analyses of synthetic GPI glycoconjugates. 156 In summary, while the total number of glycolipid determinants in glycosphingolipids and glycophospholipids is difficult to estimate, for the considerations here we will assume that the glycolipid repertoire of glycan determinants is B500.…”
Section: How Many Glycan Determinants Exist?supporting
confidence: 53%
“…The extrapolation of these observations to human cerebral malaria is not straightforward, however, because the abnormalities in the mouse model result from accumulation of leukocytes, rather than parasitized erythrocytes, in the cerebral blood vessels. It has been reported that lysates of P. falciparum-infected erythrocytes stimulate TNF production by human mononuclear cells, an effect which was inhibited by a monoclonal antibody recognizing a phosphatidylinositol-like epitope (8). In another study, P. falciparum pigment was found to stimulate the production of high levels of TNF-␣ and IL-1␤ by monocytes, and this activity was eliminated by treatment of the parasite pigment with protease (143).…”
Section: Cerebral Malariamentioning
confidence: 93%
“…Since the severity of clinical manifestations of malaria is correlated with the presence of tumor necrosis factor (TNF) in the circulation (8,13,15), components of parasitized erythrocytes which induce its production and cause hypoglycemia (25) are customarily referred to as toxins (11). The TNF-inducing activity is associated with a phospholipid (1,3) and is inhibited by inositol monophosphate (2). The hypoglycemia associated with malaria correlates with hyperinsulinemia (6).…”
mentioning
confidence: 99%